Docker Optimization of an Automotive Sector Virtual Server Infrastructure - Hernandez, Leonel; Uc Rios, Carlos Eduardo (Knowledge Engineering and Data Science, 2024)
Server virtualization is a powerful strategy for optimizing network infrastructure. It allows multiple virtual servers to run on a single physical server, maximizing resource utilization and improving efficiency. Deploying server virtualization using Docker technology offers a lightweight and flexible approach to optimizing network infrastructure. Docker contains package applications and their dependencies, enabling consistent and efficient deployment across various environments. Specifically, optimizing virtual server infrastructure using Docker Technology in the automotive sector focuses on improving the efficiency and management of the company's virtual server resources. By implementing Docker technology, a container platform that allows the packaging and running of applications in a lightweight and secure manner, the project aims to reduce operational costs and increase the agility and scalability of IT services. Adopting Docker will facilitate the rapid deployment of applications, ensuring a consistent and isolated execution environment for each one. This will allow the company to manage its workloads more efficiently and respond quickly to market needs, reassuring the audience about the potential improvements in their work processes. The study is developed under the top-down methodology guidelines for the design of telematics systems. It also includes a detailed analysis of the current server performance, a proposal for restructuring the existing infrastructure, and a plan to implement DevOps practices to optimize development and operational processes. With these changes, a significant improvement in system availability and performance is expected, thus contributing to the company's growth and technological innovation. The benefits of Docker implementation are numerous, including lightweight (containers share the host OS kernel, reducing overhead), portability (consistent environment across development, testing, and production), scalability (effortlessly scale containers horizontally), isolation (each container runs in its isolated environment), and efficiency (optimal resource utilization compared to traditional VMs). These benefits promise a brighter future for the company's IT infrastructure.